ASSESSMENT OF NURSE EDUCATORS PROFESSIONAL ETHICS ADHERENCE AND STUDENTS LEARNING OUTCOMES IN SCHOOL OF NURSING IN AKWA IBOM STATE - Etimbuk Ignatius Pius (Journal Park Publishing, 2022)
Ethical codes are instructions that shape ethical behavior and determine which values and beliefs should be accepted. These codes act as a practical guideline in the nursing profession. The present study aimed to examine the nurse educator’s professional ethics adherence and students learning outcomes in school of nursing in Akwa Ibom State, Nigeria. In order to carry out this study, specific research objective was drawn from which one null hypothesis was formulated and used for the study. The research design for this study is an Expost Facto design. The population of the study consisted of three hundred and thirty-eight (338) year 2 & 3 Students in the three schools of nursing in Akwa Ibom State. Simple random sampling technique was used to select 150 respondents. The instrument used for data collection was questionnaire. The instrument was validated by research experts. Cronbach Alpha reliability technique was used for testing the reliability of the instrument and reliability index of .75 was realized, hence the instrument was regard as being reliable. Data from completed questionnaires was subjected to mean analysis and Independent t-test analysis. The findings showed that there is a proportional relationship between nurse educator's professional ethics adherence and students learning outcomes in school of Nursing in Akwa Ibom State. It was recommended that Professional ethics adherence should be seen by all nurse educators as a panacea for high student academic not only in school of nursing but also in level of education that requires strict adherence to ethical issues. Hence, it should be practiced by all levels of management in order to quickly fast track and meet up with the objectives of the learning and teaching.
Keywords: Nurse Educators; Professionalis; Ethics; Adherence